Expanding the boundary of brand extensions through brand relationship quality - Arikan, Esra; Yilmaz, Cengiz; Bodur, Muzaffer (Journal of Business Economics and Management, 2016)
Research on brand extensions identifies the concept of perceived fit as the prime determinant of success. Yet, it is not difficult to find examples of brands that have been extended successfully into “perceptually distant” domains. In an attempt to resolve this discrepancy between research insights and practical experiences, the study investigates the role of Brand Relationship Quality (BRQ) as a critical factor determining consumer responses to brand extensions. The proposed model is tested separately in the context of three different fit scenarios (high, moderate, and low) with data from 502 consumers. The results indicate that BRQ and perceived fit exert independent effects on consumer responses and complement each other as they jointly influence evaluations of brand extensions. The study therefore extends existing theory by providing evidence that the brand extension phenomenon cannot be explained justly without including constructs that portray personal relationships consumers develop with brands and provides insights for marketers and researchers as to how such relationships can be integrated in formulations of successful brand extension strategies.